Prevalence and Acquisition Risk Factors of Methicillin- Resistant Staphylococcus aureus in Swine-Production Personnel in Chiang Mai and Lamphun Provinces, Thailand - Peerapat Rongsanam (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The emergence of livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) in swine farms worldwide including Thailand has posted public health concern. Healthy pigs in farms in Chiang Mai and Lamphun provinces colonized with SCCmec-IX MRSA strains were previously reported. However, knowledge of prevalence and acquisition factors of MRSA among swine production personnel (SPP) who might be at risk due to occupational exposure to pigs and farm environments are still limited. Therefore, this study aimed to address the MRSA carriage rate and acquisition risk factors among SPP in Chiang Mai and Lamphun provinces. Data of 202 voluntary SPP and 31 swine farms in Chiang Mai and Lamphun provinces were collected during February-August 2017. All SPP nasal samples were screened for MRSA, that are subject to biochemical and antimicrobial susceptibility testing, multiplex PCR, and staphylococcal cassette chromosome (SCC) mec typing. The prevalence of MRSA was calculated at 7.9% (16/202) among SPP and 19.3% (6/31) among swine farms. All 59 MRSA isolates were multidrug resistant which 83-93% of all isolates were resistant to clindamycin, tetracycline, and ciprofloxacin. Nearly all isolates (55/59, 93%) were classified as SCCmec IX-MRSA which is livestock related clone. Data analysis showed that level of education, working time in the farm, frequency of contact with pigs and working solely on swine production, were risk factors of MRSA acquisition (p < 0.05). In addition, good personal hygiene including shower after work (p = 0.005) and changing work cloths before leaving the farm (p = 0.019) significantly associated with MRSA carriage. The number of staff and pigs in farm, duration of disease outbreak, the implementation of suitable methods for vehicle disinfection and personal disinfection, and water quality control significantly associated with MRSA prevalence in farm (p < 0.05). Moreover, usage of tetracycline drugs significantly related to MRSA detection (p = 0.046). The multivariate regression analysis showed that the experience of working with pigs (adjusted OR 0.92, 95% CI 0.83 - 1.03, p = 0.141), working days per week (adjusted OR 4.2, 95% CI 0.98 - 18.05, p = 0.053), and shower after working (adjusted OR 0.14, 95% CI 0.04 - 0.49, p = 0.002) were good predictors for MRSA carriage among SPP (AUC = 0.84). This study revealed that relatively high prevalence of SCCmec IX-MRSA among SPP in Chiang Mai and Lamphun provinces was associated with occupationally exposure of MRSA, inappropriate personal and farm hygienic practices and antimicrobial usage. The study population could be potential source of MRSA infection and transmission in household and community, therefore, awareness and active monitoring of MRSA in swine production as well as good agricultural practice in swine farms were recommended to prevent the dissemination of MRSA.